The relation between prototypical and marginal morphology - Schwaiger, Thomas (Linguistica (Ljubljana), 2011)
The article investigates a paradigm case of a borderline phenomenon in linguistic analysis: constructions in which linguistic material is meaningfully iterated (or repeated) and their relation to prototypical and marginal areas of morphology. The fuzzy state of affairs prevailing in this research area is described and a survey of relevant and irrelevant iteration phenomena is undertaken. The discussion finally narrowing in on morphological reduplication, the data dealt with (mostly) come from the typologically oriented Graz Database on Reduplication (gdr). In light of certain data encountered there (i.e. reduplicative imperatives and a pragmatically emphatic vowel copying construction), the morphological process of reduplication is further differentiated, the general term reduplicative construction (Moravcsik 1978) thereby being endowed with a special meaning subsuming both prototypical and marginal instances of the process under scrutiny, couching the investigation into a morphological framework along lines similar to those proposed by Zwicky/Pullum (1987) and Dressler (2000). The study concludes with a tentative general picture of repetition phenomena in language in which grammaticalization theory can comprehensively account for such constructions that linguistically range from discourse to morphology. Finally, the potential benefit of the present approach for any typological undertaking in the realm of the reduplication process is highlighted.
Keywords: constructions réduplicatives; marginalno oblikoslovje; morfologija; morphologie; morphologie marginale; morphologie prototypique; oblikoslovje; podvojitvene konstrukcije; podvojitvene zgradbe; prototipsko oblikoslovje